Developing risk awareness among young people: an essential component in preparing young people for the world of work. (1st March 2011) - Stone, N
Abstract : Every 40 min, a young person will have been injured at work in Great Britain. In the last 10 years, 66 under-19s have been killed at work. All the evidence suggests that young people, particularly in the agriculture and construction sectors, have a higher than average risk of being killed or injured in the workplace. There is a small but significant group of employers who do not take these legal responsibilities seriously and fail to ensure proper training and supervision. The British Safety Council (BSC) is playing its part through funding entry level health and safety awareness qualifications for all 14–19 year olds in full time education in the UK before they embark on work experience or their first job. BSC has set aside 0.5m of its charitable funds each year over the period 2007–2017 to make that commitment reality. In its second year, 2007/08 this qualification reached 40% of UK secondary schools. Although there is still a long way to go to make this important opportunity available and accessible to all young people preparing for the world of work the early signs from emerging evidence are that the training and qualification are helping to better equip young people to understand and help manage the risk of injury and ill-health they will face in the workplace. Evaluation of the effectiveness of this programme will be available in time to share with those attending the 2010 conference.